2013
DOI: 10.3126/jfl.v11i1.8612
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation in Nepal: Exploring Ways to Overcome the Barriers

Abstract: Abstract: Abstract: Abstract: Adaptation to climate change is emerging as an important developmental challenge in Nepal and globally. To address climate change risks and vulnerabilities, a set of mutually integrated strategies are necessary at different sectors and levels. This paper examines institutional, technological and informational barriers to designing and implementing adaptation. In particular, it combines literature review and case studies to diagnose the limitation of adaptation and its institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Because of climate change it is reported untimely start of monsoon rainfall that resulted rain deficit in the eastern Terai lowlands in 2005/06, reducing crop production by 12.5% nationwide (Malla, 2008). In agriculture, about 10% of agricultural land was left fallow due to rain deficit on the one hand, while on the other hand in the Midwestern Terai faced heavy rain with floods, which reduced crop production by 30% (Regmi & Bhandari, 2013). The participants of the FGD responded higher temperature, erratic rainfall, hailstones, drought and landslides in last decades that had affects in subsistence agriculture of Kamalamai Municipality.…”
Section: People Perception On Climate Changementioning
confidence: 99%
“…Because of climate change it is reported untimely start of monsoon rainfall that resulted rain deficit in the eastern Terai lowlands in 2005/06, reducing crop production by 12.5% nationwide (Malla, 2008). In agriculture, about 10% of agricultural land was left fallow due to rain deficit on the one hand, while on the other hand in the Midwestern Terai faced heavy rain with floods, which reduced crop production by 30% (Regmi & Bhandari, 2013). The participants of the FGD responded higher temperature, erratic rainfall, hailstones, drought and landslides in last decades that had affects in subsistence agriculture of Kamalamai Municipality.…”
Section: People Perception On Climate Changementioning
confidence: 99%
“…In Nepal, numerous studies have been performed on the effects of climate change on agriculture [8] [13] [22] [23] [24] [25], rice production [15] [16] [26] and climate change adaptation [24] [27] [28] [29] [30] [31]. Despite the interest in climate change adaptations at the local and regional levels, little literature is available on issues such as determinants, perceptions and barriers that affect the adoption of climate change adaptation options for rice production.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Devkota, Phuyal & Shrestha (2017) identified that rural rice farmers have adopted 12 different adaptation options to prevent themselves from climatic anomalies. Several previous studies (Jones & Byod, 2011;Regmi & Bhandari, 2013) show that such adaptation is not easy to the rural level due to various diseconomies of scale. Such studies argued that rice production and its productivity in Nepal has been facing several constraints and challenges related to socio-economic and infrastructures that lead to low level of productivity (Joshi, 2017).…”
Section: Introductionmentioning
confidence: 94%